Diagnostic accuracy of three-dimensional transvaginal ultrasound for intrauterine adhesions: a systematic review and meta-analysis - Huang, Liyin; Huang, Zhiping; Hu, Bijuan (Frontiers in Medicine, 2025)
BackgroundIntrauterine adhesions (IUA) are a common cause of menstrual abnormalities, infertility, and adverse pregnancy outcomes. Hysteroscopy is the diagnostic gold standard but is invasive and less accessible in some clinical settings. Three-dimensional transvaginal ultrasonography (3D-TVUS) offers a non-invasive alternative; however, its diagnostic accuracy for IUA remains uncertain.ObjectiveTo systematically evaluate the diagnostic performance of 3D-TVUS for detecting IUA, using hysteroscopy as the reference standard.MethodsA systematic review and meta-analysis were conducted following PRISMA-DTA guidelines. PubMed, Wiley library, Web of Science, Cochrane Library, and major Chinese databases were searched up to August 1, 2025. Eligible diagnostic accuracy studies reported sensitivity, specificity, or data allowing construction of 2 × 2 tables. Two reviewers independently screened studies, extracted data, and assessed quality using QUADAS-2. A bivariate random-effects model was used to pool sensitivity, specificity, positive and negative likelihood ratios (PLR, NLR), diagnostic odds ratio (DOR), and hierarchical summary receiver operating characteristic (HSROC) curve.ResultsNine studies involving 2,830 participants were included. The pooled sensitivity was 0.86 (95% CI: 0.83–0.89) and specificity was 0.90 (95% CI: 0.87–0.92). The pooled PLR and NLR were 8.6 (95% CI: 6.2–11.9) and 0.16 (95% CI: 0.13–0.20), respectively. The pooled DOR was 53.2 (95% CI: 34.7–81.4). The HSROC curve yielded an area under the curve (AUC) of 0.94 (95% CI: 0.91–0.96), indicating high diagnostic accuracy. Fagan’s nomogram demonstrated a substantial increase in post-test probability following a positive test result and a marked decrease following a negative result.Conclusion3D-TVUS demonstrates high sensitivity, specificity, and overall accuracy for diagnosing intrauterine adhesions, supporting its potential as a reliable, non-invasive first-line diagnostic tool. Further multicenter, prospective studies with standardized imaging protocols are warranted to validate these findings and optimize clinical application.